(untitled) (Research, Society and Development, 2021)
Stroke is defined as a neurological pathology with three main subtypes: subarachnoid hemorrhage, intracerebral hemorrhage and cerebral ischemia. Comparing the ischemic event in relation to the hemorrhagic, there is greater incidence of Ischemic Stroke, which originates about 85% of the cases. Thus, this retrospective observational study sought to describe the prevalence of psychiatric illnesses, the used medication class and association between sex and age with illnesses in patients with a history of stroke with outpatient care between 2015 and 2019. The statistical tests used were Fisher and Chi-squared, with significance level α=0,05. The prevalence of depression was 53% and anxiety disorder 16% in this study. There was an association of higher prevalence of vascular dementia and epilepsy (p=0,05) in male patients. Therefore, psychiatric pathologies such as depression and anxiety have a high prevalence in patients with a history of stroke, requiring multiprofessional monitoring.